Monitoring system reaction in cyber-physical testbed under cyber-attacks. (April 2017) - Bernieri, Giuseppe; Etchevés Miciolino, Estefanía; Pascucci, Federica; Setola, Roberto
Highlights: An emulator for water distribution infrastructure is introduced. Cyber-attacks models have been developed according to the Control Theory perspective. Classic Fault Diagnosis systems are not able to correctly manage cyber-attacks. How Intrusion Detection System improves the protection effectiveness is illustrated. Graphical abstract: Abstract: In this paper, we exploit the cyber-physical testbed developed within the EU Project FACIES to analyze how monitor systems, typically used in Industrial Control Systems, may be prone to fail when facing cyber-attacks. Specifically, through several experimental trials, we test the poor ability of a Fault Diagnosis module to correctly manage cyber-attacks, which generally turn to be considered physical faults, forcing operators to perform erroneous countermeasures. To conclude, we outline how the presence of a cyber Intrusion Detection System improves the effectiveness and the reliability of the protection schema. The experimental validation has been carried out on an emulated water distribution system.